Corrosion of weldment made on austenitic steel X2CrNi18-9 caused by sigma phase - Marzena Lachowicz (Przegląd Spawalnictwa, 2017)
The paper presents results of the research performed in order to determine causes of corrosion of the part made of austenitic steel of the X2CrNi18-9 grade. In particular the corrosion was observed in the areas of welded joints. It has been found that the cause of the corrosion was presence of the sigma phase precipitated during welding of the tested structural components. Also, it has been found that austenite shows the anodic character in relation to the sigma phase, which led to initiation of corrosion pits, as a result of the galvanic effect created, and further development of the corrosion.